Geographic distribution extension of Anoura cadenai and comments on Sturnira giannae distribution in Colombia - García-Restrepo, Sebastián; Amórtegui-Hernández, Daniela; Arenas, Camilo; Carrasquilla Ferro, María Cristina; González, Camila (Therya Notes, 2023)
Although Colombia holds a high richness of Chiroptera, many taxa and geographic areas remain unexplored. In this study, we confirm the presence of Anoura cadenai and Sturnira giannae in new geographical regions and update the information about its distribution in the country. Through the review of field-collected individuals and specimens deposited in the Mammal Collection of the C. J. Marinkelle Natural History Museum (ANDES-M), we evaluated the concordance and variations of several external and craniodental traits with respect to the original descriptions. The records of A. cadenai on the eastern mountain range showed a distributional extension from the western and central mountain ranges. Sturnira giannae is widely distributed along the eastern mountain range, the inter-Andean valley of the Magdalena River, and the western mountain range’s western slope. Unlike the original descriptions of both bat species, we found our specimens had smaller external and craniodental sizes. This is the first report of Anoura cadenai in the Eastern Mountain Range and in sympatry with A. latidens. Regarding S. giannae, we report its occurrence in the inter-Andean valley of the Magdalena River and reaching the western slope of the Western Mountain Range. This broadens the previously suggested distribution up to the eastern slopes of the Andes. More extensive specimen reviews in biological collections could provide new information about the distribution of these species in Colombia.